Development of a finite-discrete element method with finite-strain elasto-plasticity and cohesive zone models for simulating the dynamic fracture of rocks. (April 2023) - Wu, Di; Li, Haibo; Fukuda, Daisuke; Liu, Hongyuan
Abstract: This paper implements a finite-strain-based Mohr-Coulomb (MC) elasto-plastic model into the combined finite-discrete element method (FDEM) with the intrinsic cohesive zone model (ICZM). The formulation of elasto-plastic continuum elements based on the concept of unrotated configuration as the frame of reference is firstly incorporated into an in-house FDEM code, which is parallelized by general-purpose graphic processing units. The developed FDEM code can not only handle the finite elasto-plastic deformation, the large displacement, and the rotation of continuum elements but also simultaneously model the explicit rock fracturing. The split Hopkinson pressure bar (SHPB)-based dynamic tests, single-hole blasting, and model blasting experiments reported in the literature are then modeled using the FDEM with and without the MC model to elucidate the effects of the incorporation of the MC model on the dynamic rock fracturing simulation results. It is elucidated that the conventional FDEM tends to show more fractures and undesirable overestimations of local stresses and particle velocities while the proposed FDEM can reasonably avoid these issues in all the numerical simulations conducted in this study.